Microfluidics technologies and applications - Lin, Bingcheng; Basuray, S. (Sagnik) (Topics in Current Chemistry2, 2011)
S. Shoji K. Kawai Flow Control Methods and Devices in Micrometer Scale Channels L. Capretto W. Cheng M. Hill X. Zhang Micromixing Within Microfluidic Devices S. Zeng X. Liu H. Xie B. Lin Basic Technologies for Droplet Microfluidics L. Wang X. Gong W. Wen Electrorheological Fluid and Its Applications in Microfluidics J. Noh H. C. Kim T. D. Chung Biosensors in Microfluidic Chips S. Senapati S. Basuray Z. Slouka L.-J. Cheng H.-C. Chang A Nanomembrane-Based Nucleic Acid Sensing Platform for Portable Diagnostics H. Gai Y. Li E. S. Yeung Optical Detection Systems on Microfluidic Chips S. K. Njoroge H.-W. Chen M. A. Witek S. A. Soper Integrated Microfluidic Systems for DNA Analysis J. K. Osiri H. Shadpour M. A. Witek S. A. Soper Integrated Multifunctional Microfluidics for Automated Proteome Analyses C. Zhang D. van Noort Cells in Microfluidics W. Shi H. Wen B. Lin J. Qin Microfluidic Platform for the Study of Caenorhabditis elegans